Dwelling in performing as thinking - Vittori, Giulia (Mimesis Journal, 2013)
Merging Heidegger’s thought with the work of the Théâtre du Radeau, I aim at finding a philosophical way of describing the act of performing, and some of its philosophical implications, outside of the horizon of representation. Phenomenology and ontology are applied to theatre mostly with respect to directing and spectating; in the field of performance studies, they are used to read performance as social behavior, leaving theatre behind. Instead, my emphasis on Heidegger’s ontology is directed to consider the phenomenon of performing as a domain of actors and from the aesthetic point of view per se. Emphasizing the experience of the actor and of her lexicon to retell it, I aim at showing how Heidegger’s thought on Being reveals important insights to reconsider the theatrical event as an act of knowledge. I argue that both the philosopher and the artists of Radeau, by rejecting the methodologies, results, and implications of representations, make of the artwork a process for the unconcealment of Being. Laurence Chable’s words on her experience as an actress at Radeau show how performing constitutes a privileged training in embodying such a process. Putting this philosopher and this theatre company in conversation helps locate the role of theatre as a prominent one in the contemporary aesthetic horizon. Such dialogue extends the idea of the work of art as ontic experience to the practice of performing, and suggests to conceive the function of performing as enacted Weltanschauung. The event of the performance becomes in this way a place for welling, with props that become things and actors that become poets.